Engineering the plant genome, transient gene silencing, meristematic gene expression and up regulation of flowering - The phase change in papaver bracteatum - Phani Raja Kumar Madam (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
CRISPR - Cas9 for gene editing has long been considered revolutionary in minimizing time frame to improve plant genetics and crop breeding. By using CRISPR tools we can improve desired traits, such as yield, plant height, gene expression, gene silencing, and disease tolerance. Flowering in plants is regulated by complex network of gene-controlled factors. This paper particularly aims at CRISPR-induced double-strand breaks used to create a gene "knock-ins" by exploiting the cells' homology-directed repair. The precise insertion of a donor template can alter the coding region of a gene. Altering the Cas9 protein so it cannot cut DNA, transient gene silencing or transcriptional repression can also be done. The modified Cas9, led by a guide RNA, targets the promoter region of a gene and reduces transcriptional activity and gene expression. CRISPR/Cas9 genome-editing system based on RNA endoribonuclease to induce high-efficiency and inheritable targeted deletion of transcription factors involved in floral development in Papaver bracteatum. By using AP1, SVP, and TFL1 as the target genes, multisite and multiple-gene mutations were achieved to express multiplexed sgRNAs from a single transcript driven by the promoter in transgenic lines. Targeted deletions of chromosomal fragments between the first exon and second exon in either one or three genes were generated by using a single binary vector. Interestingly, the efficiency of site-targeted deletion was comparable to that of mutation with the multiplexed sgRNAs. DNA sequencing analysis of RT-PCR products showed that targeted deletions of AP1 and TFL1 may lead to frameshift mutations of the target genes. In addition, no RT-PCR amplified product was acquired after SVP targeted deletion. Furthermore, the targeted deletions resulted in abnormal floral development in the mutant lines compared to that of un-treated plants. AP1 and SVP mutations increased plant branching expressively, while treated mutant plants displayed a change from indeterminate to determinate inflorescences. Results demonstrate that CRISPR/Cas9 with the RNA endoribonuclease Csy4 processing system is an efficient tool to study floral development and improve floral traits rapidly and phase change from Juvenility to flowering phase was tracked using shoot apical meristematic genes by vernalization and other gene editing factors.